Decision Support System for Determining Employee Shift in Hospital. Bhayangkara Tk. II Medan with Simple Additive Weighting (SAW) Method - Desi Hotnida Pasaribu (International Journal of Basic and Applied Science, 2021)
This study is a Decision Support System for determining employee shifts using the Simple Additive Weighting (SAW) method of the SAW method, which is looking for a weighted sum of performance ratings on each alternative on all criteria, making a suitability rating table for each alternative on each specified criteria and make a decision matrix. The application that is built is a web-based application using the PHP programming language and using a MySQL database. The purpose of this study is to solve the problem of Employee Shift computerized, with the existence of this system the Hospital. Bhayangkara Kindergarten. II Medan can provide fast and accurate information.